PENGARUH MUSIK KLASIK TERHADAP HASIL BELAJAR PADA MAHASISWA PSIKOLOGI DI UNIVERSITAS MUHAMMADIYAH GORONTALO - Zulkarnain Zulkarnain; Putri Febriani Talib; Karisma Busura; Megawati M Amir Sirua; Rosniawatu S Umar; Alda Ibrahim (program studi psikologi, 2024)
Classical music has long been thought to have a positive influence on various aspects of human cognition, including learning ability. This research aims to analyze the influence of classical music on student learning outcomes. By using an experimental method on 60 students divided into two groups (experimental group and control group), this research found that students who listened to classical music while studying showed significantly improved learning outcomes compared to the group who studied without music. The results of this research provide important implications for the development of more effective learning strategies.